2001
DOI: 10.1074/jbc.m103864200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Endogenous SsrA-tagged Proteins Reveals Tagging at Positions Corresponding to Stop Codons

Abstract: The SsrA⅐SmpB quality control system adds a C-terminal degradation peptide (AANDENYALAA) to nascent chains on stalled ribosomes, thereby freeing the ribosome and ensuring proteolysis of the tagged protein. An SsrA mutant with the tag sequence AANDEHHHHHH was used to slow degradation and facilitate Ni 2؉ -nitrilotriacetic acid affinity purification. Display of affinitypurified Escherichia coli proteins on two-dimensional gels revealed small quantities of a diverse set of SsrA-H 6 -tagged proteins, and mass spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
145
2
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(156 citation statements)
references
References 33 publications
8
145
2
1
Order By: Relevance
“…In particular, the amount of several tagged protein species, which were also tagged in the hemK ϩ strains, is markedly increased. Because some of the major endogenous targets of tmRNA were tagged at their natural stop codons (21), this result may indicate that tagging at these sites is enhanced by a termination deficiency. The function of HemK identified here raises the question of how it leads to the suppression of the light sensitivity of a protoporphyrin IX-accumulating mutant (hemH) (1).…”
Section: Discussionmentioning
confidence: 94%
“…In particular, the amount of several tagged protein species, which were also tagged in the hemK ϩ strains, is markedly increased. Because some of the major endogenous targets of tmRNA were tagged at their natural stop codons (21), this result may indicate that tagging at these sites is enhanced by a termination deficiency. The function of HemK identified here raises the question of how it leads to the suppression of the light sensitivity of a protoporphyrin IX-accumulating mutant (hemH) (1).…”
Section: Discussionmentioning
confidence: 94%
“…However, RbsK tagging depends in large part on the scarcity of the rare tRNA whereas full-length YbeL tagging is largely dependent on the chemical nature of the C-terminal residues of the nascent chain. Full-length tagging of the cI repressor (12) and UDP-galactose-4-epimerase 2 have also been observed but neither of these systems involves a C-terminal proline or a rare C-terminal codon. Perhaps other C-terminal amino acid sequences can also influence tagging via interactions with release factors or SsrA.…”
Section: Discussionmentioning
confidence: 99%
“…Because termination of translation is a relatively slow process compared with translation elongation (11), SsrA and protein release factors probably compete for binding to the A-site, while the ribosome idles at an inefficient stop codon. However, SsrA tagging of full-length proteins encoded by genes with efficient stop signals has also been observed (12). For example, the intact E. coli YbeL protein is tagged (12) even though the ybeL coding region ends with an extended UAAU stop signal which is thought to be the most efficient translation termination signal in E. coli (13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies identified six E. coli proteins (LacI, RbsK, GalE, YbeL, PhoP, and RpsG) (28,38) and eight B. subtilis proteins (EF-Tu, FolA, GsiB, TreP, PerR, YqaA, YtoQ, and YloN) (47) that are tagged by tmRNA under normal growth conditions. Only seven of these proteins are encoded in the C. crescentus genome, and only EF-Tu was identified as a tmRNA substrate.…”
Section: Discussionmentioning
confidence: 99%